One-Pot Synthesis of 2,4,5-Trisubstituted Oxazoles via a Tandem Passerini Three-Component Coupling/Staudinger/Aza-Wittig/Isomerization Reaction - Wang, Long; Ren, Zhi-Lin; Chen, Min; Ding, Ming-Wu (Synlett, 2014)
2,4,5-Trisubstituted oxazoles were prepared via a tandem Passerini three-component coupling/Staudinger/aza-Wittig/isomerization reaction in one-pot fashion, starting from easily accessible α-azidocinnamaldehydes, acids, isocyanide and triphenylphosphine.
Keywords: oxazole; tandem reaction; aza-Wittig reaction; Passerini reaction; isomerization